Strategic Partner’s Attractiveness Index for the European Union. Can the Eurasian Economic Union headed by Russia become strategic partner for the EU? - Pablo Podadera Rivera; Anna Garashchuk (Revista de Economía Mundial, 2018)
Summary Before the Ukrainian conflict the EU-Russian relationships had been developing in the format of Strategic Partnership, and Russia had been considered as one of the ‘special ten’ to whom a special status of ‘strategic partner’ was awarded. The ‘special ten’ are unequal in size, political regimens, resource endowments, economic development, and power status. The main problem of this new concept of European Union Foreign Policy is that there is neither an official definition of strategic partnership nor any common criteria for being chosen as a strategic partner. It is worth mentioning that Russia at the same time has not only developed the integration with the European Union but has also promoted the integration in the post-Soviet area and as a result the Eurasian Economic Union (EEU) has been created. Thus, speaking about the UE-Russian relations we should take into account the new Actor on the international arena, the EEU. The present paper aims at elaborating Strategic Partner’s Attractiveness Index for the EU, using the categorical principal components analysis (CATPCA). This analysis allows us to rank its declared strategic partners and to find out which position Russia and other members of the EEU hold in a rank.